Sickness absence associated with shared and open-plan offices – a national cross sectional questionnaire survey - Pejtersen, Jan H.; Feveile, Helene; Christensen, Karl B.; Burr, Hermann (Scandinavian Journal of Work, Environment & Health, 2011)
' ' OBJECTIVE ': 'The aim of this study was to examine whether shared and open-plan offices are associated with more days of sickness absence than cellular offices. ' ' METHODS ': 'The analysis was based on a national survey of Danish inhabitants between 18–59 years of age (response rate 62%), and the study population consisted of the 2403 employees that reported working in offices. The different types of offices were characterized according to self-reported number of occupants in the space. The log-linear Poisson model was used to model the number of self-reported sickness absence days depending on the type of office; the analysis was adjusted for age, gender, socioeconomic status, body mass index, alcohol consumption, smoking habits, and physical activity during leisure time. ' ' RESULTS ': 'Sickness absence was significantly related to having a greater number of occupants in the office (P<0.001) when adjusting for confounders. Compared to cellular offices, occupants in 2-person offices had 50% more days of sickness absence [rate ratio (RR) 1.50, 95% confidence interval (95% CI) 1.13–1.98], occupants in 3–6-person offices had 36% more days of sickness absence (RR 1.36, 95% CI 1.08–1.73), and occupants in open-plan offices (>6 persons) had 62% more days of sickness absence (RR 1.62, 95% CI 1.30–2.02). ' ' CONCLUSION ': 'Occupants sharing an office and occupants in open-plan offices (>6 occupants) had significantly more days of sickness absence than occupants in cellular offices.
Keywords: office building; open-plan office; shared office; sick leave; sickness absence; work environment